Evaluation of Interface Shear Strength Coefficient of Alternative Geogrid Made from Para Rubber Sheet - Anubud Liangsunthonsit; Pakkapon Jaroonrat; Jiratchaya Ayawanna; Weerawut Naebpetch; Salisa Chaiyaput (Polymers, 2023)
is progressively smaller in reinforced sand, lateritic soil, and clay, respectively. Higher tensile strength of reinforced materials using the RCS geogrid than those using the RSS geogrid is encouraged by the better elastic characteristics of the RCS geogrid. Thus, utilizing the RCS geogrid-reinforced materials can better increase the shear strength of coarse-grained soil such as sand and gravel.
Keywords: Geotechnical Engineering and Soil Stabilization; Landfill Environmental Impact Studies; Geotechnical Engineering and Underground Structures